The determinants of employee Job satisfaction: The case of agriculture extension officers in Wanging’ombe district council, - Mbungu, Bernard Elias (Mzumbe University, 2024)
A dissertation submitted in partial fulfilment of the requirements for the degree of Master of Science in Human Resource and Management (Msc.HRM) of Mzumbe University